2008
DOI: 10.1016/j.brainres.2008.02.037
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenesis and neuronal commitment following ischemia in a new mouse model for neonatal stroke

Abstract: Stroke in the neonatal brain is an important cause of neurologic morbidity. To characterize the dynamics of neural progenitor cell proliferation and maturation after survival delays in the neonatal brain following ischemia, we utilized unilateral carotid ligation alone to produce infarcts in postnatal day 12 CD1 mice. We investigated the neurogenesis derived from the sub-ventricular zone and the sub-granular zone of the dentate gyrus subsequent to injury. Newly produced cells were labeled by bromodeoxyuridine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 34 publications
7
48
1
Order By: Relevance
“…78,79,83 Furthermore, an increase in BrdU þ cells was observed in the affected SVZ from 1 week to 3 weeks after HI, implying that cell proliferation is stimulated in this region. 14,[77][78][79]81,83,84 Interestingly, BrdU þ cells were also shown in the striatum 14,77,78,81,83 and cortical regions 14,77,82 from 1 to 4 weeks after the insult. This finding suggests that either proliferating cells in the SVZ migrate to these regions or that local progenitors proliferate because of molecular changes in the cell environment.…”
Section: Neurogenesis After a Hypoxic-ischemic Insultmentioning
confidence: 95%
See 1 more Smart Citation
“…78,79,83 Furthermore, an increase in BrdU þ cells was observed in the affected SVZ from 1 week to 3 weeks after HI, implying that cell proliferation is stimulated in this region. 14,[77][78][79]81,83,84 Interestingly, BrdU þ cells were also shown in the striatum 14,77,78,81,83 and cortical regions 14,77,82 from 1 to 4 weeks after the insult. This finding suggests that either proliferating cells in the SVZ migrate to these regions or that local progenitors proliferate because of molecular changes in the cell environment.…”
Section: Neurogenesis After a Hypoxic-ischemic Insultmentioning
confidence: 95%
“…Accumulating evidence suggests that HI injury promotes extensive cell proliferation in the SVZ of the rodent brain. 14,[77][78][79][80][81][82][83] Several studies in which P6 and P7 rats and P10 mice were subjected to moderate HI showed that the SVZ expands in size, illustrated by increased cresyl-violet staining and nestin-positive cells in the ipsilateral SVZ. 78,79,83 Furthermore, an increase in BrdU þ cells was observed in the affected SVZ from 1 week to 3 weeks after HI, implying that cell proliferation is stimulated in this region.…”
Section: Neurogenesis After a Hypoxic-ischemic Insultmentioning
confidence: 99%
“…Acute postligation seizure activity was scored according to a seizure rating scale as previously reported [6,9].…”
Section: Acute Seizure Scoringmentioning
confidence: 99%
“…Brain atrophy measurements were done as previously described [9] using MCID 7.0 Elite (InterFocus Imaging Ltd.) to measure hemispheric areas of Nissl-stained coronal serial sections spanning rostral striatum to caudal hippocampus (n = 10-12 sections per animal). Total subgranular zone (SGZ) lengths were measured by tracing the SGZ contours using MCID in every DG in which SGZ BrdUpositive cells were quantified.…”
Section: Computerized Measurement Of Atrophy and Subgranular Zone Lengthmentioning
confidence: 99%
See 1 more Smart Citation